A agradabilidade facial do perfil de indivíduos Nipo-Brasileiros sob a percepção de diferentes culturas - Santos, Alexandre Magno dos (2018)
Objectives: to evaluate Japanese-Brazilian adult individuals in relation to their facial acceptability in different cultures and to verify the correlation between cephalometric values and facial attractiveness. Material and Methods: the sample consisted of 82 Japanese-Brazilian subjects (42 females and 40 males) with a muscle-facial balance, represented by passive lip sealing, absence of orthodontic treatment or previous facial surgery. Profile photographs were evaluated by 3 ethnic groups: Brazilian Caucasians, Japanese-Brazilians and Japanese, who were composed of laypeople, orthodontists and Bucomaxillofacial Surgeons. Individuals were classified as aesthetically acceptable, pleasant and unpleasant. Cephalometrics of all individuals were performed to verify the mean values, to compare them with the values of Brazilian Caucasians and to verify if there was a correlation of the values with the pleasantness. The statistical tests performed were: Kendall's concordance coefficient, chi-square and proportions test, Spearman correlation coefficient and the t-test. In all tests, a significance level of 5% (p<0.05) was adopted. Results: most individuals were considered aesthetically acceptable. In the aesthetically unpleasant individuals, the nose, mouth and chin were the structures that most impacted their faces. The mean values of the Japanese-Brazilian subjects were: Nasolabial Angle of 100.70º, Mentolabial Angle of 139.89º, Interlabial Angle of 127.84º, Facial Convexity Angle of 9.87º, Total Angle of Convexity of 121.73º, Angle of the lower third of the Face of 113.03º, MAFH/LAFH Proportion of 0.84 and Proportion of the Lower Third of the Face of 0.51. When compared to Caucasians, Japanese-Brazilians have a more closed nasolabial angle, greater protrusion of the upper and lower lip and decreased facial convexity than Caucasians. The excess of the lower third in relation to the middle third of the face was greater in xantodermas. The proportion of the lower third of the face was better in the xantodermas. Conclusion: the evaluation of the facial pleasantness is important to direct the diagnosis and the acceptability of the patient regarding their ethnicity. Knowledge of these characteristics should be considered by the professionals involved in the treatment.